The oil of Carapa (Carapa spp. Meliaceae) in West Africa: uses and implications in the conservation of natural tree stands - (:unkn) unknown (My University, 2010)
The tree. Trees in the genus Carapa (Meliaceae) grow in all African tropical forests along the Equator, from the Albertine Rift region to Southern Senegal and Mali. In Africa, as well as in South America, carapa trees are the source of valuable timber and non-timber forest products (NTFP). Fruit and seeds. A typical carapa fruit consists of a capsule with four to five valves, each enclosing two to five seeds, i.e., a total of eight to twenty seeds per fruit. Oil extraction. Village inhabitants strive to collect seeds that have fallen to the ground before they get infested or germinate, which is detrimental to oil quality. The oil is extracted after the seeds have been boiled. Carapa oil has a broad application range and is used more frequently than the extracts from leaves, bark or root. Market. The carapa oil trade in Africa has a primarily local orientation, and the commercialization of the oil is rudimentary. However, the use of carapa oil as a natural repellent in the cultivation of organic cotton is expected to create an increased demand for oil production. Discussion. With regard to the high economic potential of carapa oil, its commercialization needs to provide the producers with equitable revenue for the efforts to render it profitable. Measures to protect carapa populations and their habitats are needed to allow for the long-term production of carapa oil. The plantation of trees appears to be a sustainable approach for the conservation of natural carapa tree stands.
Keywords: African Research